2018
DOI: 10.2196/jmir.9196
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Visit Notes on Patient Portals for Engaging Less Educated and Nonwhite Patients: Survey Study

Abstract: BackgroundOpenNotes, a national initiative to share clinicians’ visit notes with patients, can improve patient engagement, but effects on vulnerable populations are not known very well.ObjectiveOur aim is to examine the importance of visit notes to nonwhite and less educated patients.MethodsPatients at an urban academic medical center with an active patient portal account and ≥1 available ambulatory visit note over the prior year were surveyed during June 2016 until September 2016. The survey was designed with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 37 publications
(45 reference statements)
5
53
0
Order By: Relevance
“…Open notes might be viewed as extending the visit, potentially thereby elongating and strengthening patient–physician interactions before and after the pressures of the clinical encounter 1 3 4. It is reasonable to postulate that this perceived elongation of the visit through online access to notes may reduce anxiety, negative emotions and poor recall associated with stereotype threat 14.…”
Section: Opportunity To Improve Health Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…Open notes might be viewed as extending the visit, potentially thereby elongating and strengthening patient–physician interactions before and after the pressures of the clinical encounter 1 3 4. It is reasonable to postulate that this perceived elongation of the visit through online access to notes may reduce anxiety, negative emotions and poor recall associated with stereotype threat 14.…”
Section: Opportunity To Improve Health Equitymentioning
confidence: 99%
“…However, for many reasons, persons from these demographic groups are less likely to use health portals than other patient populations 5. Drawing on promising preliminary evidence,2–4 6 we suggest that open notes may, over time, prove important in the care of patients who are at risk of experiencing healthcare disparities.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have demonstrated that reading clinical notes can be essential to understanding the health condition and care plans, and encouraging patients' engagement in their decision making regardless of having a medical degree. 42,44 Employees who accessed only the EHR and did not have a MHAV account still viewed their notes more than any other document in the EHR. Although they did not message their providers through our studied information systems, they read the messages sent between care team members.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Studies of OpenNotes have evaluated the patients' understanding of their health conditions, recalling care plans, and participation in shared decision making. 42,43 In one study to evaluate granting access to minority patients to read their clinical notes, authors found that black, Hispanic, and Asian patients indicated that reading notes was highly important. 43 Another study found that patients who read at least four clinical notes in a year were more likely to be involved in the decision-making process of their care plan.…”
mentioning
confidence: 99%